The Effect of Social Media Advertising, E-Wom and Price on Consumer Purchase Decisions in Buying Skincare Products at E-Commerce Shoppe - Adrian Muhamad Fajar; Sri Astuti Pratminingsih (Jurnal Ilmu Manajemen Advantage, 2022)
This study aims to determine the effect of social media advertising, electronic word of mouth and prices on skincare purchasing decisions at Shopee. This research uses a quantitative approach with a population of student consumers at the Faculty of Economics and Business, Widyatama University. The sampling technique uses the purposive sampling method by taking samples through the Google Form Questionnaire which is distributed online. The sample was distributed to 100 respondents according to the research criteria. The data analysis technique uses multiple regression. The results of the study explain that social media advertising variables have a significant effect on skincare purchasing decisions with a significant value of 0.000 <0.05. Electronic word of mouth variables have a significant effect on skincare purchasing decisions with a significant value of 0.010 <0.05. Meanwhile, the price variable does not have a significant effect on skincare purchasing decisions at Shopee with a significant value of 0.071 > 0.05. The results of the coefficient of determination (R) are independent (social media advertising, electronic word of mouth and price) simultaneously by obtaining an R Square value of 41.9%.